2011
DOI: 10.21000/jasmr11010090
|View full text |Cite
|
Sign up to set email alerts
|

Reforestation Guidelines for Unused Surface Mined Lands: Development, Application and Adoption

Abstract: Abstract. More than 600,000 hectares of mostly forested land in the Appalachian region were surface mined for coal under the Surface Mining Control and Reclamation Act. Today, these lands are largely unmanaged and covered with persistent herbaceous species, such as fescue and serecia lespedeza, and a mix of invasive and native woody species with little commercial or ecological value. Some landowners and surrounding residents would like to restore native forests on some of these lands for the valuable products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Focal issues for reclamation are site stabilization, restoration of the original contours, and re-vegetation (SMCRA, 2006). Focus on soil erosion and vegetation coverage means reclamation can be approved without consideration for other biota (Mummey et al, 2002a, b;Burger et al, 2011;Buehler and Percy, 2012). Even in this specific focus, reclamation may not appropriately meet long-term vegetation objectives (Holl, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Focal issues for reclamation are site stabilization, restoration of the original contours, and re-vegetation (SMCRA, 2006). Focus on soil erosion and vegetation coverage means reclamation can be approved without consideration for other biota (Mummey et al, 2002a, b;Burger et al, 2011;Buehler and Percy, 2012). Even in this specific focus, reclamation may not appropriately meet long-term vegetation objectives (Holl, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines have been developed through ARRI to promote mine reclamation efforts that will expedite the establishment of native hardwood forest on active (e.g., Burger et al, 2005) and legacy mine lands (Burger et al, 2011). Encouraging structural complexity and floristic richness similar to natural forest would maximize bird species recolonization in a variety of restoration settings (Twedt et al, 2002;Munro et al, 2011).…”
Section: Prioritizing For Reclamationmentioning
confidence: 99%
“…2). Mine reclamation guidelines developed through the Appalachian Regional Reforestation Initiative (ARRI) promote restoration of native hardwood forest conditions on active mines (Burger et al, 2005) and legacy mine lands (Burger et al, 2011). Reforesting mined lands adjacent to existing forest can reduce negative edge and area effects on interior forest species thus improving suitability for forest-dependent birds such as Cerulean Warblers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies and field applications of these minerals have been reported, providing environmental and technological solutions to the aforementioned industrial activities, including: i) the uptake of pollutants from wastewaters (Itskos et al, 2010;Moreno et al, 2001;Querol et al, 2006;Balsamo et al, 2012Balsamo et al, , 2010; ii) agriculture (Guaya et al, 2018;Gholamhoseini et al, 2013); iii) ecological restoration and soil amendments (Buondonno et al, 2013;Burger et al, 2011;Larney and Angers, 2012;Vallejo et al, 2012); and iv) organics waste composting (; Nissen et al, 2000;Villaseñor et al, 2011;Zorpas et al, 2000). Attention has also been paid to the synthesis of K-zeolites from fly ash and its potential applications have also been of interest and lead to a series of studies focused mainly on the synthesis of philipsite and chabazite for potential agriculture purposes (Amrhein et al, 1996;Murayama et al, 2008;Querol et al, 1997;Zeng et al, 2002) The interest on K-zeolites has been grown in the last years in view of its potential application in agriculture as slow release fertilizers.…”
Section: Introductionmentioning
confidence: 99%